EXPOSING SOCIAL INEQUALITY FROM THE MENTALLY ILL REPRESENTATION IN TODD PHILLIPS’ JOKER - Marsena, Jennifer Gracia; Angjaya, Sonny (Lire Journal (Journal of Linguistics and Literature), 2022)
Social inequality has continuously become a problem especially towards marginalized group. Such topic is presented in Todd Phillips latest psychological thriller, Joker (2019). Whilst other researches focus on the psychological aspect of the film, this study takes on the perspective of the sociological/socio-political aspect in the film which is social inequality. In analyzing the social inequality aspect of the film, this study uses theory of structural discrimination by Link, et al. which theorizes that laws, policies, or other practices. are discriminating a marginalized group. To analyze the film itself, the writers analyzed the mise-en- scène and cinematography aspects of the film. The purpose of this study is to find if government’s policies have any involvement of impact to the life of a mentally ill person. Method used for this analysis is qualitative data research. In analyzing the film, it is found that Fleck’s life as a mentally ill and poor person is deliberately sabotaged by the discriminative policies and laws applied in Gotham city. In conclusion, this film represents Joker as more than just a Batman’s main film but rather used as a vehicle to criticize the state of social inequality in the world.